"Domestic Houseflies" and "Giant Cucumbers": Virginia Woolf's Feminist Literary Criticism and Women Writers of the Long Eighteenth Century. Issue 2 (3rd April 2023) - Vandenberghe, Fauve
ABSTRACT: Virginia Woolf's A Room of One's Own (1929) is frequently considered the single most influential work that helped establish feminist literary criticism as a discipline. It continues to be a key feminist text today: scholars avidly debate how Woolf's criticism instigated, but also thwarted and distorted, the study of women's literary history. Apart from A Room, Woolf also engaged extensively with women's literary history both in her fictional and non-fictional writing. I argue that it is important to put A Room in dialogue with both Woolf's early essays about eighteenth-century women writers and her writing about literary history and aesthetics. Re-reading A Room in light of this is a useful exercise because it helps us understand that Woolf's feminist literary history project is not solely based on women's economic entrance into the literary marketplace, but that, for Woolf, literary aesthetics played an important part in women's inclusion or exclusion in literary history. In examining Woolf's conception of women's literary history of the long eighteenth century, this essay sheds new light on the close entanglement of aesthetics and feminist politics in Woolf's writing.